Peripheral Blood Derived Mononuclear Cells Enhance the Migration and Chondrogenic Differentiation of Multipotent Mesenchymal Stromal Cells - Niina Hopper; John Wardale; Daniel Howard; Roger Brooks; Neil Rushton; Frances Henson (Hindawi Limited, 2015)
A major challenge in cartilage repair is the lack of chondrogenic cells migrating from healthy tissue into damaged areas and strategies to promote this should be developed. The aim of this study was to evaluate the effect of peripheral blood derived mononuclear cell (PBMC) stimulation on mesenchymal stromal cells (MSCs) derived from the infrapatellar fat pad of human OA knee. Cell migration was measured using an xCELLigence electronic migration chamber system in combination with scratch assays. Gene expression was quantified with stem cell PCR arrays and validated using quantitative real-time PCR (rtPCR). In both migration assays PBMCs increased MSC migration by comparison to control. In scratch assay the wound closure was 55% higher after 3 hours in the PBMC stimulated test group (P=0.002), migration rate was 9 times faster (P=0.008), and total MSC migration was 25 times higher after 24 hours (P=0.014). Analysis of MSCs by PCR array demonstrated that PBMCs induced the upregulation of genes associated with chondrogenic differentiation over 15-fold. In conclusion, PBMCs increase both MSC migration and differentiation suggesting that they are an ideal candidate for inclusion in regenerative medicine therapies aimed at cartilage repair.